Relationships between Spirituality, Happiness, and Prosocial Bystander Behavior in Bullying-The Mediating Role of Altruism - Fernanda Inéz García-Vázquez; Maria Fernanda Durón-Ramos; Rubén Pérez-Rios; Ricardo Ernesto Pérez-Ibarra (MDPI AG, 2022)
Positive psychology is vital in increasing prosocial behavior and reducing bullying. However, limited studies have analyzed the influence of positive personal characteristics on the prosocial behaviors of bystanders in bullying. The present study examined direct and indirect relationships between spirituality, happiness, altruism, and prosocial bystander behavior in bullying. Participants in this study were 685 students from Northwestern Mexico; 51% were male and 49% female, between 12 and 18 years old (M = 14.3 years, SD = 1.68). A structural equation model (SEM) was calculated. The results indicate that happiness and altruism were related to prosocial bystander behavior. Spirituality and happiness have an indirect relationship by increasing prosocial bystander behavior through the positive effects of altruism. The SEM explained 48% of the variance of the prosocial bystander. The implications for improving defensive behavior in bullying and reducing school violence are discussed.